2011
DOI: 10.1002/adsc.201100139
|View full text |Cite
|
Sign up to set email alerts
|

Highly Regioselective Isomerization–Hydroformylation of Internal Olefins Catalyzed by Rhodium/Tetraphosphine Complexes

Abstract: A new class of substituted tetraphosphine ligands has been applied in the rhodium-catalyzed regioselective isomerization-hydroformylation of internal olefins. The rhodium/tetraphosphine ligand system is highly effective for the isomerization and hydroformylation of 2-alkenes to form linear aldehydes. Greater than 95% linear selectivity and up to 94% yield of the total aldehydes were obtained for 2-pentene, 2-hexene and 2-octene. The catalyst system also showed high to moderate linear selectivity for the isomer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
15
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 40 publications
0
15
0
Order By: Relevance
“…[12] Other examples are the isomerisation of allyl benzenes such as estragol or safrole, which are of great interest for the fragrance industry. [13,14] A wide range of isomerisation catalysts have been developed based on various metals such as Pd, [15][16][17] Ru, [18][19][20][21][22] Ti, [23][24][25] V, [26] Fe, [27][28][29] Rh, [30][31][32] Mo, [33] Ni, [34][35][36] etc., but also metal-free systems such as frustrated Lewis pairs. [37] One of the most active catalysts is the ruthenium-based "alkene zipper" developed by Grotjahn and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…[12] Other examples are the isomerisation of allyl benzenes such as estragol or safrole, which are of great interest for the fragrance industry. [13,14] A wide range of isomerisation catalysts have been developed based on various metals such as Pd, [15][16][17] Ru, [18][19][20][21][22] Ti, [23][24][25] V, [26] Fe, [27][28][29] Rh, [30][31][32] Mo, [33] Ni, [34][35][36] etc., but also metal-free systems such as frustrated Lewis pairs. [37] One of the most active catalysts is the ruthenium-based "alkene zipper" developed by Grotjahn and co-workers.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Boerner and co‐workers employed a phosphite ligand in the I‐HF of isomeric n ‐octenes, leading to better linear selectivity (up to 48 % n ‐nonanal) . Thus, a literature survey suggested that both (bis)phosphites and bisphosphine can catalyze isomerizing functionalization reactions of internal alkenes at elevated temperatures (120–140 °C) . Among the long‐chain plant oils, linear selective I‐HF of methyl oleate is found to be catalyzed by bisphosphite ligands of type L1 (Figure ) …”
Section: Resultsmentioning
confidence: 99%
“…Several rhodium-based systems were developed in industry and academia for this demanding reaction. [17] Thus, the ruthenium-catalyzed hydroformylation of 2-octene was also investigated (Table 2). Unfortunately, no conversion was obtained by applying the standard reaction conditions developed for terminal alkenes (100 8C, 0.1 mol % Ru; Table 2, entry 1).…”
Section: Resultsmentioning
confidence: 99%